The possible impact of passive smoke exposure on radiation-related risk estimates for lung cancer among women: the life span study of atomic bomb survivors. (2nd November 2021) - Hu, Audrey E.; French, Benjamin; Sakata, Ritsu; Bhatti, Parveen; Bockwoldt, Brandie; Grant, Eric J.; Phipps, Amanda I.
Abstract: Purpose: Analyses of the Life Span Study cohort of atomic bomb survivors have shown a statistically significant sex difference in the excess risk of incident lung cancer due to radiation exposure, with the radiation-related excess relative risk per gray (ERR/Gy) for women approximately 4 times that for men, after accounting for active smoking. We sought to determine the extent to which this risk difference could be explained by adjustment for passive smoke exposure, which is a known risk factor for lung cancer that was not measured among Life Span Study participants, and which could be particularly influential among female never-smokers. Materials and methods: The Life Span Study includes survivors of the atomic bombings of Hiroshima and Nagasaki and city residents who were not in either city at the time of the bombings, matched to survivors on city, sex, and age. First primary lung cancers were identified from population-based cancer registries between 1958 and 2009. Data on active smoking were obtained from mailed surveys and in-person questionnaires (1965–1991). We calculated passive smoke exposure for female never-smokers by attributing smoking pack-years at various intensities (5–50%) based on smoking patterns among men, stratified by city, birth year, radiation dose, and lung cancer status. Poisson regression models with additive and multiplicative interactions between radiation dose and smoking were used to estimate sex-specific radiation-related excess relative risks for lung cancer. Results: During the study period, 2, 446 first primary lung cancers were identified among 105, 444 study participants. On average, male smokers started smoking 19.5 cigarettes per day at 21.5 years old. Partially attributing male smoking patterns to female never-smokers—to approximate passive smoke exposure—yielded lower radiation-related ERR/Gy estimates for women under a multiplicative radiation-smoking interaction model, leading to a lower female-to-male ratio of ERR/Gy estimates; however, this difference was evident only at very high passive smoke intensities. Under an additive radiation-smoking interaction model, the results were unchanged. Conclusions: Our results are consistent with the possibility that failure to account for passive smoke might contribute, in small part, to the higher radiation risk estimates for lung cancer among women compared to men in the Life Span Study.